Online Drug Purchasing in India: Community Pharmacists Perceptions and Attitudes - Subodh S Satheesh; Viswanatham Sai Lakshmi; Sigma Surbhi; Shreyas PR (National Journal of Community Medicine)
Background: In India, online pharmacies have gained significant popularity and are reshaping the way in which pharmaceutical services are provided. With community pharmacist serving as an integral part of public health, promoting the safe and effective use of medicines, this study aimed to evaluate their perceptions of online pharmacies.